First experimental release of the red-and-green macaw Ara chloropterus in Corrientes, Argentina - Volpe, Noelia Laura (2017)
In 2015 seven captive-bred red-and-green macaws Ara chloropterus were experimentally released into the Iberá National Park, Corrientes, Argentina. After a month in a pre-release cage, they were hard released. Two birds were preyed upon, three flew beyond our detection range, one transmitter was recovered underwater, and one bird was recaptured. We identify ways in which future releases of captive-bred macaws could be improved.